The Future of Induced Pluripotent Stem Cells for Cardiac Therapy and Drug Development - Thorrez, Lieven; Sampaolesi, Maurilio (Current Pharmaceutical Design, 2011)
The field of stem cell research was revolutionized with the advent of induced pluripotent stem cells. By reprogramming somatic cells to pluripotent stem cells, most ethical concerns associated with the use of embryonic stem cells are overcome, such that many hopes from the stem cell field now seem a step closer to reality. Several methods and cell sources have been described to create induced pluripotent stem cells and we discuss their characteristics in terms of feasibility and efficiency. From these cells, cardiac progenitors and cardiomyocytes can be derived by several protocols and most recent advances as well as remaining limitations are being discussed. However, in the short time period this technology has been around, evidence emerges that induced pluripotent stem cells may be more prone to genetic defects and maintain an epigenetic memory and thus may not be entirely the same as embryonic stem cells. Despite the lack of a complete fundamental understanding of stem cell biology, and even more of ways how to coax them into defined cell types, the technology is quickly adopted by industry. This paper gives an overview of the current applications of induced pluripotent stem cells in cardiovascular drug development and highlights active areas of research towards functional repair of the damaged heart. Adult stem cells have already been taken to clinical trials and we discuss these results in light of potential and hurdles to be taken to move induced pluripotent stem cells to the clinic.
Keywords: stem cells